Peran Dinas Pariwisata dalam Pengelolaan Kebersihan Lingkungan sebagai Upaya Mendukung Pariwisata Berkelanjutan di Kampung Wisata Kereng Bangkirai - Winey, Viona Okvelin; Sintha, Deasy Eka; Friskila, Octavia Alva; Santoso, Yonatan Ari (Al-Ijtima`i: International Journal of Government and Social Science, 2026)
Environmental cleanliness plays an important role in supporting sustainable tourism, as it affects destination perception, tourist satisfaction, and environmental sustainability, especially in tourist areas that are directly adjacent to local communities. This study aims to examine the role of the Palangka Raya City Tourism Office in managing environmental cleanliness in the Kereng Bangkirai Tourism Village as part of efforts to realize sustainable tourism. The results of the observation show that cleanliness management differs between the front area and the inner part of the tourist area. It also shows that inter-agency coordination and community participation are not yet optimal. This study conducted descriptive qualitative research using interviews, observation, and documentation. The results show that the tourism sector is responsible for acting as a regulator, dynamizer, facilitator, and motivator in environmental cleanliness management. However, its implementation has not been fully optimal due to low collective awareness in some communities, inconsistent participation of the Tourism Awareness Group (Pokdarwis), and a lack of cross-sector coordination. Supporting factors include policy support and the availability of sanitation facilities, while inhibiting factors include limited resources and a lack of coordination among stakeholders.